Effects of local enemal matrix protein on osseointegration of different surface Titanium implants - Ozmen Istek; Kevser Sokmen; Erhan Cahit Ozcan; Murat Tanrisever; Turker Gelic; Umit Koray Can; Alihan Bozoglan; Serkan Dundar (Revista Científica)
The aim of this study is to investigate the osseointegration levels of implants with different surfaces locally applied with enamel matrix protein by biomechanical methods. Thirty adult female Spraque Dawley rats weighing 300–350 g were included in the study as subjects. The rats were divided into 3 groups with 10 rats in each group: Machined Surface Group (n = 10), Sandblasted Large Acid Grid (SLA) Surface Group (n = 10) and Resorbable Blasting Material (RBM) Surface Group (n = 10). Titanium implants were surgically placed in the right tibias of the rats with sterile physiological serum cooling. Immediately before the implants were placed, local enamel matrix protein was applied to the prepared sockets and then the implants were placed. The rats were euthanized after waiting for osseointegration for four weeks and the implants were taken with the surrounding bone tissues after the soft tissues were removed. The bone–implant contact of all implants was analyzed by biomechanical method and recorded in Newton·cm-1 (N·cm-1). When the obtained biomechanical data were examined, the average bone–implant contact value was found to be 2.24 ± 0.67 (N·cm-1) in machined surface implants, 4.5 ± 1.36 (N·cm-1) in SLA surface implants and 3.24 ± 0.94 (N·cm-1) in RBM surface implants. A statistically difference was detected between machined surface implants and SLA surface implants (P<0.05; P=0.02). It can be stated that local enamel matrix protein application may increase bone–implant connection in SLA surface implants.